NATO and the North Atlantic revitalising collective defence - Olsen, John Andreas 1968- (Whitehall paper series, 2017)
"NATO will need to respond effectively to Russia's return to the North Atlantic. Moscow's increased military activity over the past few years gives reason for concern. The priority Russia has placed on military reform and power projection in a time of economic austerity; the scale and scope of Russia's programmed and 'snap' military exercises in the Arctic Ocean, Barents Sea and Baltic Sea; and the revamping of the Northern Fleet, including the establishment of a new Arctic Command, add urgency to those concerns. Beyond this, Vladimir Putin seeks to secure Russian access to warm-water ports in the Black Sea and the Mediterranean that could provide logistic support for naval forces deployed to the Atlantic. Stronger and more capable armed forces are preconditions for Russia to re-emerge as a regional great power with global reach, and Russia is steadily shaping its navy to support these aims. Russia has not only engaged in a major upgrade of its sea-based deterrent forces and is strengthening its sea-based antiballistic missile systems, but is also investing in strategic-level anti-surface warfare capability. Although the Russian Federation Navy is not on a par with the former Soviet Navy, it is developing high-end strategic capabilities that could potentially disrupt sea operations and project force into the Atlantic Ocean, as well as deny Allied maritime operations in the strategic waters between Greenland, Iceland, the UK and Norway. Russia has made it a strategic priority to re-establish an offensively oriented navy for operations in the North Atlantic. Putin's offensive stance is very popular with the Russian population; to many he represents the counterweight to the United States and its allies in Europe. Russia is committed to revitalising and updating the bastion concept and this will remain the defining factor for NATO defence planning in the northern region in the foreseeable future. The Kremlin's long-range power projection strategy presents a major challenge to all NATO members and partners. This 'second coming' in the North Atlantic is the new strategic reality for European security: in broader terms, the 'new normal'."--Publisher's website.